2011
DOI: 10.4028/www.scientific.net/amr.317-319.254
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Consumer-Oriented Product System Design

Abstract: This paper deeply discussed consumer kansei system and demand, based on Kansei Engineering system; it researched method of product system design. This method used application theory of Kansei Engineering: consumer decision-aid system and designer decision-aid system, which investigated consumers’ preference adjectives in terms of kansei image, then used product system design, and outputted corresponding specific form of product system. On the other hand, product system designed by designers would induce the aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…As apart of the continuing study of the thermochemistry of hydrate alkalis borates, Liu et al [29][30] also reported the thermodynamic properties of two hydrated cesium borates by adiabatic calorimeter. In his paper, the standard molar enthalpies of formation of β-CsB Thermodynamic properties play very important roles in industrial and scientific applications, especially in the field of model parameters of Pitzer and its extend ion interaction model, which can be used for determining other thermodynamic properties and predicting solubility of electrolytes if the corresponding parameters were obtained.…”
mentioning
confidence: 99%
“…As apart of the continuing study of the thermochemistry of hydrate alkalis borates, Liu et al [29][30] also reported the thermodynamic properties of two hydrated cesium borates by adiabatic calorimeter. In his paper, the standard molar enthalpies of formation of β-CsB Thermodynamic properties play very important roles in industrial and scientific applications, especially in the field of model parameters of Pitzer and its extend ion interaction model, which can be used for determining other thermodynamic properties and predicting solubility of electrolytes if the corresponding parameters were obtained.…”
mentioning
confidence: 99%